Integrating Forward Modeling and Deep Learning for Precise Detection of Geological Anomalies in Coal Seams Using the Radio Imaging Method - Shun Yang; Yanqing Wu; Yinan Zhao; Mingwei Liu; Peng Lu; Zhifang Liu (IEEE Access)
The radio imaging method (RIM) is a non-destructive detection technique widely used in geophysical surveys and monitoring. However, it currently faces challenges in accurately detecting geological anomalies. To enhance detection accuracy, we propose a novel approach that integrates forward modeling and the deep learning UNet semantic segmentation architecture, termed the FM-UNet method. We first construct a forward model that reflects the geological characteristics of the target exploration area and validate it using field RIM survey data. Next, we use the RIM data generated from the forward model for inversion and construct the training dataset. Finally, we apply the deep learning UNet architecture to accurately predict the locations of geological anomalies within the exploration region. Our results demonstrate that the FM-UNet method effectively reduces the false geological anomaly (FGA) areas and significantly improves detection accuracy compared to traditional methods. Additionally, we compared the performance of four UNet architectures, with the Transformer UNet achieving the best results: the average ratio of FGA decreased by 37.37%, and the mean intersection over union (IoU) and average F1 score increased by 24.26% and 23.78%, respectively, confirming the feasibility of our approach.